Long-term Clinical and Radiological Outcomes after Central Decompressive Laminoplasty for Lumbar Spinal Stenosis - Kim, Jun-Hwan (Korean J Spine, 2017)
OBJECTIVE: There are many technical modifications of decompressive lumbar laminectomy. The purpose of this study was to report long-term clinical and radiological outcomes of central decompressive laminoplasty (CDL), the corresponding author’s own modification of lumbar laminectomy for lumbar spinal stenosis (LSS). METHODS: Among 100 patients who underwent CDL by a single surgeon between December 2010 and March 2014, 68 patients were included in this study. Mean follow-up time was 37.7 months. Clinical and radiological data were gathered prospectively and reviewed retrospectively. Clinical outcome was measured by using visual analog scale (VAS) for back/buttock and leg, and the Oswestry Disability Index (ODI). Radiological outcome was measured by neutral slippage percentage, dynamic slippage percentage, and dynamic intervertebral angel on sagittal X-ray. Outcomes after CDL were assessed by changes of clinical and radiological parameters from the baseline. Mixed effect model with random patients’ effect as used to test for differences in the repeated measured clinical and radiological data. RESULTS: The patients had no serious complications with an uneventful recovery during the early postoperative period. In the early postoperative period, VAS scores for back/buttock and leg improved significantly and were kept with time (p<0.001). ODI also improved significantly during the postoperative follow-up period (p<0.001). The radiologic parameters were well maintained and showed no progression of instability. During the follow-up, a case of herniated disc at same level recurrence was noted after lifting trauma, and 2 adjacent foraminal stenosis needed additional surgery. CONCLUSION: CDL provides long-term pain relief and functional restoration without progression of radiological instability.